Employment in long-term care: Report on Poland - Stanislawa Golinowska; Ewa Kocot; Agnieszka Sowa (Center for Social and Economic Research (CASE), 2014)
The report discusses the formal long-term care workforce in Poland. It presents past and future trends in the development of LTC employment. Authors collected scattered statistical information, estimated lacking data and projected future growth in the number of employed in care services. Performed analysis includes employment in the health and social sector and across various types of care. Projections of the demand for care and supply of the LTC workforce base on the demographic prognosis of the population size and changes in the age structure taking into account different scenarios for demographic development. Results show the growing gap between demand and supply in the LTC employment. The policy towards aging in Poland will must take up the challenge of growing care needs, family changes and lower opportunities for provision of informal care.
Keywords: H51; H53; H75; I18; 330; Long-term Care; Employment in Long-term Care; Employment Projections; Labour Resources in Long-term Care; Medical and Care Professions